Catalytic enantioselective desymmetrisation as a tool for the synthesis of hodgkinsine and hodgkinsine B. - Snell, R; Durbin, M; Woodward, R; Willis, M; Snell, R; Durbin, M; Woodward, R; Willis, M (2012)
Two palladium-catalysed amination protocols are deployed in the desymmetrisation of the complex dimeric alkaloid meso-chimonanthine. The power of these transformations is showcased in an efficient formal and total synthesis of the natural products hodgkinsine and hodgkinsine B, respectively.